Efficiency of Different Disinfectants on Bacillus cereus Sensu Stricto Biofilms on Stainless-Steel Surfaces in Contact With Milk - Silva, Higor Oliveira; Lima, Joyce Aparecida Santos; Aguilar, Carlos Eduardo Gamero; Rossi, Gabriel Augusto Marques; Mathias, Luis Antonio; Vidal, Ana Maria Centola (Frontiers in Microbiology, 2018)
The species of the B. cereus group have the ability to adhere to and form biofilms on solid surfaces, including stainless steel, a material widely used in food industries. Biofilms allow for recontamination during food processing, and the “clean-in-place” (CIP) system is largely used by industries to control them. This study thus proposes to evaluate the efficacy of peracetic acid and sodium hypochlorite against biofilms induced on stainless-steel surfaces. The SAMN07414939 isolate (BioProject PRJNA390851), a recognized biofilm producer, was selected for biofilm induction on AISI 304 stainless steel. Biofilm induction was performed and classified into three categories: TCP (Tyndallized, Contaminated, and Pasteurized milk), TCS (Tyndallized milk Contaminated with Spores), and TCV (Tyndallized milk Contaminated with Vegetative cells). Subsequently, the coupons were sanitized simulating a CIP procedure, on a pilot scale, using alkaline and acid solutions followed by disinfectants (peracetic acid and sodium hypochlorite). Microorganism adhesion on the surfaces reached 6.3×105 to 3.1×107 CFU/cm-2. Results did not show significant differences (p>0.05) for surface adhesion between the three tested categories or (p>0.05) between the two disinfectants. Microbial populations adhered to the stainless-steel coupons are equally reduced after treatment with peracetic acid and sodium hypochlorite, with no differences in the control of B. cereus s.s. biofilms on AISI 304 stainless-steel surfaces.